Biomimetic and bioinspired silicifications: Recent advances for biomaterial design and applications. (15th January 2021) - Abdelhamid, Mohamed A.A.; Pack, Seung Pil
Abstract: The rational design and controllable synthesis of functional silica-based materials have gained increased interest in a variety of biomedical and biotechnological applications due to their unique properties. The current review shows that marine organisms, such as siliceous sponges and diatoms, could be the inspiration for the fabrication of advanced biohybrid materials. Several biomolecules were involved in the molecular mechanism of biosilicification in vivo . Mimicking their behavior, functional silica-based biomaterials have been generated via biomimetic and bioinspired silicification in vitro . Additionally, several advanced technologies were developed for in vitro and in vivo immobilization of biomolecules with potential applications in biocatalysis, biosensors, bioimaging, and immunoassays. A thin silica layer could coat a single living cell or virus as a protective shell offering new opportunities in biotechnology and nanomedicine fields. Promising nanotechnologies have been developed for drug encapsulation and delivery in a targeted and controlled manner, in particular for poorly soluble hydrophobic drugs. Moreover, biomimetic silica, as a morphogenetically active biocompatible material, has been utilized in the field of bone regeneration and in the development of biomedical implantable devices. Statement of Significance: In nature, silica-based biomaterials, such as diatom frustules and sponge spicules, with high mechanical and physical properties were created under biocompatible conditions. The fundamental knowledge underlying the molecular mechanisms of biosilica formation could inspire engineers and chemists to design novel hybrid biomaterials using molecular biomimetic strategies. The production of such biohybrid materials brings the biosilicification field closer to practical applications. This review starts with the biosilicification process of sponges and diatoms with recently updated researches. Then, this article covers recent advances in the design of silica-based biomaterials and their potential applications in the fields of biotechnology and nanomedicine, highlighting several promising technologies for encapsulation of functional proteins and living cells, drug delivery and the preparation of scaffolds for bone regeneration. Graphical abstract: Image, graphical abstract